The Effect of Good Corporate Governance Components on Tax Aggressiveness (An Empirical Study of Mining Companies on the Indonesia Stock Exchange from 2020 to 2022) - Mulyani, Ni Komang Santhi; Badera, I Dewa Nyoman (Dinasti Publisher, 2025)
Tax aggressiveness refers to corporate measures taken to minimize tax obligations, whether through lawful tax avoidance or unlawful tax evasion. This research seeks to offer empirical proof regarding the influence of good corporate governance components on tax aggressiveness. The elements of good corporate governance analyzed include independent commissioners, audit committees, institutional ownership, and managerial ownership. Moreover, the research incorporates controlled variables, company age, and profitability. The sample comprised 43 firms selected using purposive Sampling methods were employed to select the research subjects. The dataset was processed through multiple linear regression analysis. The findings indicate that independent board members do not exert a notable influence on tax aggressiveness, whereas audit committees and holdings by institutional investors significantly affect tax aggressiveness, and managerial ownership shows no effect on tax aggressiveness.